A lightly Fe-doped (NiS2/MoS2)/carbon nanotube hybrid electrocatalyst film with laser-drilled micropores for stabilized overall water splitting and pH-universal hydrogen evolution reaction. Issue 34 (12th August 2020) - Li, Chenyu; Liu, Mingda; Ding, Hanyuan; He, Liqiong; Wang, Enze; Wang, Bolun; Fan, Shoushan; Liu, Kai
Abstract : Fe-(NiS2 /MoS2 )/CNT serves as an active and stable hybrid-electrocatalyst for overall water splitting in alkali and the HER in a pH-universal environment. Abstract : Transition metal compounds are considered as competitive candidates for efficient noble-metal-free electrocatalysts in overall water splitting. However, a single material generally fails to maintain simultaneous activities in both the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Herein, we developed a hybrid electrocatalyst of a Fe-(NiS2 /MoS2 )/carbon nanotube (CNT) film by combining composite and doping strategies, followed by a microstructure design of laser-drilled micropores, for high-efficiency overall water splitting and pH-universal HER. The charge transfer between MoS2 and NiS2 synergistically enhances both the HER and OER, and the light Fe doping further promotes the synergistic effect. The microstructure with periodic pores favors the release of bubbles, ensuring long-term stabilities at both low and large current densities without activity degradation. Consequently, Fe-(NiS2 /MoS2 )/CNT exhibits an ideal voltage, even lower than that of noble-metal electrodes, of 1.51 V at 10 mA cm −2 for overall water splitting in 1 M KOH, with η 10 of the HER/OER at 87/234 mV, respectively. As a cathode, it also delivers low η 10 values of 98 mV in 0.5 M H2 SO4 and 127 mV in 1 M PBS, showing a pH-universal HER activity. Our work provides a comprehensive strategy towards high-efficiency electrocatalysts for overall water splitting, which will find a broad range of green energy applications.